Răspuns :
[tex]( \frac{2}{ \sqrt{3} } - \frac{ \sqrt{3} }{2} + \frac{1}{3 \sqrt{3} } ) \div \frac{ \sqrt{3} }{5} \\ \frac{7}{3 \sqrt{3} } - \frac{ \sqrt{3} }{2} ) \times \frac{ \sqrt{3} }{5} \\ \frac{5}{6 \sqrt{3} } \times \frac{ \sqrt{3} }{5} \\ \frac{1}{6} [/tex]
a = ( 2/√3 - 3/2√3 +1/3√3 ) : 5/√3
a = 5/6√3 × √3/5
a = 1/6
a^-1 = 1/6^-1 = 6 deoarece orice expresie ridicata la puterea -1 da întotdeauna inversul ei.
a = 5/6√3 × √3/5
a = 1/6
a^-1 = 1/6^-1 = 6 deoarece orice expresie ridicata la puterea -1 da întotdeauna inversul ei.